Nausea and vomiting in pregnancy (NVP) in Chinese pregnant women: a cross-sectional study - Tong Zou; Zhiwen Long; Silu Wang; Qiang Yao (BMC, 2024)
Abstract Background This study addresses the scarcity of research on nausea and vomiting in pregnancy (NVP) in China. It aims to explore the current NVP status in the country using validated questionnaires, analyze associated factors, and provide a useful reference for future research. The study also compares results from different assessment tools. Methods Online questionnaires were utilized to gather data from 535 pregnant women across 24 provinces. Demographic, pregnancy, and NVP-related information were collected. NVP severity was assessed using Pregnancy-Unique Quantification of Emesis and Nausea (PUQE) and the Rhodes Index of Nausea, Vomiting, and Retching (RINVR) scales. Ordinal logistic regression identified factors linked to NVP severity. Differences between PUQE and RINVR assessments were compared. Results NVP prevalence exceeded 90%, with 96.1% assessed by PUQE and 90.8% by RINVR. Incidence decreased from nausea to retching and vomiting. Severe NVP correlated with reduced gestational weight gain, younger age, fewer gestational weeks, and living in North (all P values < 0.05). There was moderate consistency between PUQE and RINVR assessments. The NVP prevalence assessed by the PUQE is higher than that assessed by the RINVR in the same population. However, the proportion of NVP levels above moderate assessed by RINVR is greater than that assessed by PUQE. Conclusions NVP is highly prevalent among Chinese pregnant women, with nausea being predominant. RINVR assessments may be better able to identify severe NVP, thereby improving the low treatment rates for severe NVP.